Can resveratrol attenuate testicular damage in neonatal and adult rats exposed to 2,3,7,8-tetrachlorodibenzo-p-dioxin during gestation? - Erthal, Rafaela P.; Siervo, Glaucia E. M. L.; Silveira, Livia T. R. [UNESP]; Scarano, Wellerson R. [UNESP]; Fernandes, Glaura S. A. (Csiro Publishing, 2018)
2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) is considered one of the most toxic dioxins. The effects of TCDD are exerted via binding to the aryl hydrocarbon receptor (AhR). The aim of the present study was to evaluate the possible protective effects of resveratrol, an AhR antagonist, against testicular damage caused by TCDD exposure during pregnancy. Pregnant female Sprague-Dawley rats were divided into four groups: a control group; a group treated with 1 mu g kg(-1), p.o., TCDD on Gestational Day (GD) 15; a group treated with 20 mu g kg(-1), p.o., resveratrol on GD10-21; and a group treated with both TCDD and resveratrol. Rats were weighed and killed, and neonatal testes were collected for histopathological analysis on Postnatal Day (PND) 1. At PND90, adult male rats were killed and the testes collected for histopathological analysis and determination of sperm count. Resveratrol had a protective effect against the effects of TCDD on Sertoli cell number in adult and neonate testes, as well as against the effects of TCDD on abnormal seminiferous tubules in adults. Combined administration of TCDD and resveratrol altered the kinetics of spermatogenesis and the proportion of neonatal testicular compartments compared with the control group In addition, combined TCDD and resveratrol treatment decreased seminiferous tubule diameter in adult male rats compared with the control group. In conclusion, resveratrol may protect against some TCDD-induced testicular damage, but, based on the parameters assessed, the administration of resveratrol and TCDD in combination may result in more severe toxicity than administration of either drug alone.
Keywords: postnatal developmental; Sertoli cell; testis